Associations of Factor VIII and von Willebrand Factor with Age, Race, Sex, and Risk Factors for Atherosclerosis - Conlan, Maureen G; Folsom, Aaron R; Finch, Andrea; Davis, C E; Sorlie, Paul; Marcucci, Gretchen; Wu, Kenneth K; For the ARIC Study Investigators (Thrombosis and Haemostasis, 1993)
Several coagulation proteins have been implicated as possible risk factors for the development of atherosclerotic diseases, among which are factor VIII and von Willebrand factor. As part of the Atherosclerosis Risk in Communities (ARIC) Study, a prospective study designed to assess risk factors for the development of atherosclerotic diseases, baseline measurements of factor VIII and von Willebrand factor (vWF) were performed to determine their relationship to the development of atherosclerosis. We herein report the associations of factor VIII and vWF with constitutional, lifestyle, and biochemical factors. Factor VIII and vWF were strongly correlated with each other (r = 0.73), and, therefore, had similar associations with risk factors. Mean levels of both factors were higher in women than in men, in blacks than in whites, and increased with age. In univariate analysis, both were positively associated with diabetes, body mass index, waist-to-hip ratio, serum insulin, and plasma triglycerides. Both were negatively associated with alcohol intake, educational level, physical activity (with some exceptions), and HDL-cholesterol. No correlations were observed between factor VIII or vWF and plasma LDL-cholesterol or lipoprotein(a). Although factor VIII was negatively associated with smoking in both sexes, vWF was not associated with smoking status. Most of these associations were confirmed in multivariate analysis. The strongest associations observed were of factor VIII and vWF with race and diabetes. In multivariate analysis, blacks had factor VIII and vWF levels 15 to 18 percentage points higher than whites, and diabetics had factor VIII and vWF levels 11 to 18 percentage points higher than non-diabetics. These associations must be taken into account when analyzing the possible role of factor VIII and vWF in the development of atherosclerotic diseases.